Antarctica as a 'natural laboratory' for the critical assessment of the archaeological validity of early stone tool sites. (April 2023) - Eren, Metin I.; Bebber, Michelle R.; Buchanan, Briggs; Grunow, Anne; Key, Alastair; Lycett, Stephen J.; Maletic, Erica; Riley, Teal R.
Abstract: Abstract : Lithic technologies dominate understanding of early humans, yet natural processes can fracture rock in ways that resemble artefacts made by Homo sapiens and other primates. Differentiating between fractures made by natural processes and primates is important for assessing the validity of early and controversial archaeological sites. Rather than depend on expert authority or intuition, the authors propose a null model of conchoidally fractured Antarctic rocks. As no primates have ever occupied the continent, Antarctica offers a laboratory for generating samples that could only have been naturally fractured. Examples that resemble artefacts produced by primates illustrate the potential of 'archaeological' research in Antarctica for the evaluation of hominin sites worldwide.